A detailed experimental and numerical assessment of the QAV – 1/anhydrous ethanol blends in their lower flammability limits - Rios Escalante, Edwin Santiago [UNESP]; Rodriguez Coronado, Christian J.; Anadrade de Carvalho Júnior, João [UNESP] (Elsevier, 2022)
Anhydrous ethanol is an attractive alternative to be used as a substitute or additive in petroleum-based fuels aiming to ensure environmental sustainability. In Brazil, ethanol has been used as an alternative fuel in both road and air (agricultural airplanes) transport sectors. Due to that ethanol is volatile, therefore flammable in standard conditions, its explosive characteristics need to be investigated. In this work, it was made a detailed experimental assessment of Lower Flammability Limits (LFLs) from QAV – 1/anhydrous ethanol/air mixtures at different temperature and pressure conditions, where QAV – 1 is Jet fuel – A1. For the measures, it was used a flammability apparatus build according to American Standard ASTM E – 681. The experimental measures from mixtures both pure and binary were compared with the classical Le Chatelier's rule. Besides, two analytical expressions were proposed. One related to the stoichiometric concentration and another related to the specific states (geometrical approximation) of each fuel. The Absolute Relative Error (ARE) was used to identify the differences between the actual values and calculated values. However, to evaluate the goodness of fit of both distributions, two important statistic parameters were used, that is; the Average Absolute Relative Error (AARE) and Chi-Square test χ2 for the full observed data. The results have shown that, for different pressure conditions, the effect of temperature increase on the LFLs is slight in the range from 100 to 150 °C. Also, LFLs from binary blends depend strongly on both nature of fuels and the size of the combustion chamber used. Additionally, it was observed that Le Chatelier's rule applied to experimental data distribution is more adequate for the prediction of LFLs, improving in less presence of fuel molecules. Finally, it using the inductive method the causes for the ignition in the LFLs were identified.
Keywords: Anhydrous ethanol; Experimental measure; Le Chateliers rule; Lower flammability limits; QAV – 1